A plasmid carrying mucA and mucB genes from pKM101 in Haemophilus influenzae and Escherichia coli. - Spikes, D (1989)
The plasmid pMucAMucB, constructed from the Haemophilus influenzae vector pDM2, and a similar plasmid, constructed from pBR322, increased the survival after UV irradiation of Escherichia coli AB1157 with the umu-36 mutation and also caused UV-induced mutation in the E. coli strain. In H. influenzae, pMucAMucB caused a small but reproducible increase in survival after UV irradiation in wild-type cells and in a rec-1 mutant, but there was no increase in spontaneous mutation in the wild type or in the rec-1 mutant and no UV-induced mutation.